2011
DOI: 10.1007/s11032-011-9661-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait locus analysis and construction of consensus genetic map for foliar disease resistance based on two recombinant inbred line populations in cultivated groundnut (Arachis hypogaea L.)

Abstract: Late leaf spot (LLS) and rust have the greatest impact on yield losses worldwide in groundnut (Arachis hypogaea L.). With the objective of identifying tightly linked markers to these diseases, a total of 3,097 simple sequence repeats (SSRs) were screened on the parents of two recombinant inbred line (RIL) populations, namely TAG 24 × GPBD 4 (RIL-4) and TG 26 × GPBD 4 (RIL-5), and segregation data were obtained for 209 marker loci for each of the mapping populations. Linkage map analysis of the 209 loci resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
224
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(243 citation statements)
references
References 39 publications
14
224
1
4
Order By: Relevance
“…Peanut (Arachis hypogaea L.) is a legume of major global importance, being grown in Asia, Africa, North America and South America, where it originated (Sujay et al, 2012;Wang et al, 2012;Mokgehle et al, 2014;Pozzi et *Corresponding author. E-mail: v inicius.agro2008.1@gmail.com.…”
Section: Introductionmentioning
confidence: 99%
“…Peanut (Arachis hypogaea L.) is a legume of major global importance, being grown in Asia, Africa, North America and South America, where it originated (Sujay et al, 2012;Wang et al, 2012;Mokgehle et al, 2014;Pozzi et *Corresponding author. E-mail: v inicius.agro2008.1@gmail.com.…”
Section: Introductionmentioning
confidence: 99%
“…A significant positive association among LLS and rust scores (0.48 to 0.60) was also reported by Anderson et al (1990). Quantitative trait locus (QTL) mapping studies have confirmed this association wherein a major QTL explaining >80% phenotypic variation (PV) for rust resistance on linkage group AhXV, recently assigned to chromosome A03, also explained 68 % PV for LLS in groundnut (Sujay et al, 2012, Pandey et al, 2017 Severe disease during pod development stage results in acute pod yield losses. Infection of LLS and rust starts from 60 DAS, therefore disease scores recorded at 75 DAS are usually low.…”
Section: Genotypic and Phenotypic Correlation Between Traitsmentioning
confidence: 64%
“…For example, the first SSRbased genetic linkage map for cultivated groundnut was recently developed for the mapping population, TAG 24 × ICGV 86031 (Varshney et al, 2009b). Subsequently five more genetic maps were developed based on mapping populations segregating for drought and foliar diseases (Gautami et al, 2012a;Ravi et al, 2011;Sujay et al, 2012). A consensus map for drought tolerance related traits with 293 SSR loci (Gautami et al, 2012a) and foliar disease resistance with 225 SSR loci (Sujay et al, 2012), respectively have been developed.…”
Section: Comprehensive Genetic Maps Andmentioning
confidence: 99%
“…Subsequently five more genetic maps were developed based on mapping populations segregating for drought and foliar diseases (Gautami et al, 2012a;Ravi et al, 2011;Sujay et al, 2012). A consensus map for drought tolerance related traits with 293 SSR loci (Gautami et al, 2012a) and foliar disease resistance with 225 SSR loci (Sujay et al, 2012), respectively have been developed. Furthermore, international collaborative efforts have resulted in the construction of consensus map with 897 SSR marker loci using genotyping data from 11 mapping populations.…”
Section: Comprehensive Genetic Maps Andmentioning
confidence: 99%